Personal Integrity and Leadership - Antonius Gea (Humaniora, 2016)
Generally, integrity is associated with leadership, especially in the organization or company. Integrity in leadership becomes a growing concern in business and organizations. The aim of this study was to find out the connection that could be shaped between personal integrity and the skill of leadership especially in the performance of work. This study used a library research, a literature study that done by using the available resources and relevant literature, related to the topic being discussed by the author. Books or journal articles related to topics were used as background reading to understand well about the problems of integrity and leadership, especially in the organization or company. This study finds out that the leader integrity is related to follower work role performance and that this effect is fully mediated through follower affective organizational commitment.